Tool for Documenting Clinical Point-of-Care Direct Observation and Formative Feedback - Sangeeta Lamba; Roxanne Nagurka (Association of American Medical Colleges, 2015)
Abstract Introduction Formative feedback during patient encounters (point-of-care) is valuable for the development of learner clinical skills since students can address gaps identified in history taking or physical exam skills, and faculty are more likely to recollect and address the identified strengths and deficiencies. Medical student ratings of direct observation and formative feedback are usually lowest in end-of-clerkship evaluations. Most clerkships use direct observation cards/checklists that do not allow for preceptors to provide the students with a global assessment of their developmental progress (i.e., what level are the students performing at and where they should be). We piloted a point-of-care tool that addresses this gap by documenting direct observation, developmental progress feedback, self-reflection and life-long learning, and student level of responsibility (direct patient contact). Methods This point-of-care tool was designed using the reporter-interpreter-manager-educator (RIME) framework to both document direct observation and provide formative feedback on a student's developmental progress. Additionally, this tool provides a uniform vocabulary to calibrate the progress of trainees. Setting level-appropriate expectations therefore guides the feedback. The tool requires medical students to self-reflect on this feedback and formulate a plan for future growth through the use of handouts such as the Point-of-Care Tool, in addition to facilitator lectures. Results We have had significant improvements in scores for end-of-clerkship statements that asked if students were directly observed obtaining history and physical examinations (moderate to high degree). The scores for resident direct observation increased more than those for attending physicians. This may be due to the fact that the tool is mainly completed by residents. On the post-clerkship survey, a majority (80%) of students in the first year of implementation were satisfied with the feedback received. The students also stated that completion of the tool for each encounter took less than a 2-3 minutes (91%). Discussion The tool is useful for a clerkship that is seeking a way to provide and document real-time feedback to learners at the bedside. The individual point-of-care entries also help learners self-reflect and create a plan of action to address their weaknesses for mid-clerkship feedback.